Effectiveness of fake news corrections using social judgement theory - Lim, Woei Lin (2019)
This study uses the framework of Social Judgement Theory (SJT) to understand how attitudes affect belief in fake news and corrections. The study revealed that the SJT concepts of ego-involvement, discrepancy and correction ambiguity predict belief in a correction, and belief in a correction subsequently predicts a decrease in fake news belief. Hence, this study has uncovered the ideal conditions for designing and targeting effective corrections to decrease fake news belief.